Marshall, Norman L., "Regional Land Use and Infrastructure Dynamics" (System Dynamic Society Records, 1993)
In almost all urban areas, existing infrastructure (transportation, water, sewer, social services) lags behind desired infrastructure. Planning new infrastructure depends on future land use forecasts. The distribution of future land use is also dependent of on available infrastructure. Due to this feedback, the infrastructure shortfall problem is resistant to solution through infrastructure improvement and local land use regulations. We have developed regional land use/infrastructure planning models that combine fairly simple system dynamics structures with spatially disaggregated databases. The models provide insights about the effectiveness of alternative policies, using detail of the local area that planners need.